Issue ownership in the online campaign for Dutch general elections - Joren Vrancken; Tom Dobber; Frederik Zuiderveen Borgesius (Journal of Digital Social Research)
Online political campaigns are often opaque, among other reasons because political parties often target their advertising to specific groups. Therefore, it is challenging for citizens, journalists, and academics to understand what political parties talk about in their campaigns, diminishing the public accountability of political parties. Through the lens of issue ownership theory, this study explores which issues Dutch political parties advertised on Meta during the 2021 national election. The study uses a relatively novel topic modeling process that is meant to limit human bias. We built a model that assigns issues to each ad (based on the ad text), creating a dataset of ad-issues matchings. The study is one of the first to present insights into the issues Dutch political parties communicated about during the national elections of 2021. Our findings show that issue owners are not the biggest advertisers on their issues and reveal that private gifts enable some political campaigns to claim ownership of many issues.